Characterisation of equivalent permeability in heterogeneous fluvial architectural elements for CO2 storage: Bunter Sandstone Formation, UK - Shakhawat Hossain; Gary J. Hampson; Carl Jacquemyn; Matthew D. Jackson; Luca Colombera (International Journal of Greenhouse Gas Control, 2026)

A machine-learning approach for classifying fluvial sandbody types from vertical facies sequences using geological analogues - Luca Colombera; Soma Budai; Nigel P. Mountney (Sedimentary Geology, 2026)

Sedimentation across a coastal plain to deep-water system: Insights from a Carboniferous succession, northern England - Sheng Chen; Adam D. McArthur; Luca Colombera; Nigel P. Mountney (Sedimentary Geology, 2026)

Capturing scales of heterogeneity in models of fluvial geothermal reservoirs: Grid resolution, upscaling strategies, and hierarchies of sedimentary architecture - Hamed Aghaei; Luca Colombera; Na Yan; Nigel P. Mountney; Odd Andersen; Andrea Di Giulio (Advances in Water Resources, 2026)

Quantitative characterisation of Quaternary glaciofluvial aquifer heterogeneity using cluster analysis - Felipe Gallardo Ceron; Landis Jared West; Ian T. Burke; James Graham; Luca Colombera (Hydrogeology Journal, 2025)
Hydrogeological modelling requires the characterisation of hydrofacies and the representation of their spatial distribution. In this work, a workflow was developed to characterise heterogeneous unconsolidated glaciofluvial sediments in Northwest Cumbria (UK), which involved: (1) field sampling; (2) lithofacies classification; (3) in situ porosity measurements using the sand-replacement method; (4) determination of the particle size distribution (PSD); (5) hydrofacies definition via K-means cluster analysis using PSD data; (6) evaluation of empirical equations for predicting porosity using field measurements and regression analysis; and (7) estimation of hydraulic conductivity ( K ) using the Kozeny–Carman equation. Nine lithofacies were identified, including glaciofluvial silts, sands and gravels, and local till deposits. Three clusters were defined on the basis of PSD: fine-dominated (cluster-1), sand-dominated (cluster-2) and gravel-dominated (cluster-3). Cluster-1 exhibited the highest porosities (average 44%); cluster-2 showed intermediate to high porosities, with an average porosity of 40%; and cluster-3 had the lowest porosities (average 27%). The logarithm of d 50 was the parameter with the highest correlation with measured porosities ( R 2 of 0.789). K values estimated using the Kozeny–Carman equation ranged between 0.06 and 0.2 m/d for cluster-1, 0.2–11 m/d for cluster 2, and 0.1–62 m/d for cluster 3. Measured porosities were higher than previously reported, while estimated K values were consistent with those from hydraulic tests. Comparison between lithofacies and clustering classification suggests that, for hydrofacies classification, the unsupervised cluster analysis approach is able to generate a classification that captures the hydrogeologically important details without creating an excessive number of categories.

Quantitative bed-type classification for a global comparison of deep-water sedimentary systems - Soma Budai; Luca Colombera; Adam McArthur; Marco Patacci (Computers & Geosciences, 2025)

Sedimentary controls on arsenic distribution in meander-belt deposits of the Po Valley, Italy - Elisabetta Bosi; Luca Colombera; Nigel P. Mountney; Duccio Bertoni; Giovanni Sarti; Alessandro Amorosi (Science of The Total Environment, 2025)

Architecture and dynamics of Precambrian linear megadunes: Galho do Miguel Formation, Mesoproterozoic, South-East Brazil - Áquila Ferreira Mesquita; Giorgio Basilici; Alexandre Ribeiro Cardoso; Carlos Roberto de Souza Filho; Nigel P. Mountney; Luca Colombera; Grace I.E. Cosgrove; Juraj Janočko; Davi Machado Querubim (Precambrian Research, 2024)

Predicting the thermal regime of the Po Plain subsurface (Italy) using geostatistical modeling constrained by legacy wells - Daniel Barrera Acosta; Giovanni Toscani; Luca Colombera; Chiara Amadori; Roberto Fantoni; Andrea Di Giulio (Marine and Petroleum Geology, 2024)

Assessing the impact of sedimentary heterogeneity on CO2 injection in fluvial meander-belt successions using geostatistical modelling informed by geological analogues - Jose M. Montero; Luca Colombera; Enrique Yuste; Na Yan; Nigel P. Mountney (International Journal of Greenhouse Gas Control, 2024)

Influence of sedimentary architecture on static connectivity and geothermal doublet performance (Mezőberény, SE Hungary) - Soma Budai; Cees J.L. Willems; Luca Colombera; Rob Westaway (Marine and Petroleum Geology, 2024)

Fracture aperture: A review on fundamental concepts, estimation methods, applications, and research gaps - Zahra Pouraskarparast; Hamed Aghaei; Luca Colombera; Enrico Masoero; Mojtaba Ghaedi (Marine and Petroleum Geology, 2024)

Mapping palaeoshorelines of river-dominated deltas in lacustrine ramp settings: Application of sedimentological analyses to the Triassic Yanchang Formation (Ordos Basin, China) - Jungang Pang; Luca Colombera; Nigel P. Mountney; Ji'an Guo; Kewen Yang; Wenhou Li (Marine and Petroleum Geology, 2024)

A 3D forward stratigraphic model of aeolian dune evolution for prediction of lithofacies heterogeneity - Na Yan; Luca Colombera; Grace I.E. Cosgrove; Nigel P. Mountney (Computers & Geosciences, 2024)

Can palaeosols reveal palaeoenvironmental variability of fluvial systems? An example from the upper portion of the Bauru Group (Upper Cretaceous, SE Brazil) - Giorgio Basilici; Paolo Lorenzoni; Áquila Ferreira Mesquita; Juraj Janočko; Luca Colombera; Grace I.E. Cosgrove; Nigel Philip Mountney; Carlos Roberto Souza Filho; Alexandre Ribeiro Cardoso; Agustín Guillermo Martinelli; Lucas Ernesto Fiorelli; Richard Guillermo Vasconez Garcia; et al. (Sedimentary Geology, 2024)

The Precambrian continental record: A window into early Earth environments - Grace I.E. Cosgrove; Luca Colombera; Nigel P. Mountney (Precambrian Research, 2024)

Multi-storey shear type buildings under earthquake loading: Adversarial learning-based prediction of the transient dynamics and damage classification - Filippo Gatti; Luca Rosafalco; Giorgia Colombera; Stefano Mariani; Alberto Corigliano (Soil Dynamics and Earthquake Engineering, 2023)

Sediment provenance and dispersal in the early Eocene Dongying Depression, Bohai Bay Basin, Eastern China: Evidence from detrital zircon geochronology, geochemistry and petrology - Ke Yang; Xiaomin Zhu; Luca Colombera; Adam McArthur; Nigel P. Mountney; Shifa Zhu; Lei Jin; Tingting Shen; Huaiyu Yang; Hongkui Chen; Shuanghui Xie; Xuling Jin (Sedimentary Geology, 2023)

Precambrian aeolian systems: A unique record? - Grace I.E. Cosgrove; Luca Colombera; Nigel P. Mountney; Giorgio Basilici; Áquila Ferreira Mesquita; Marcus Vinícius Theodoro Soares (Precambrian Research, 2023)

Quantitative analysis of aeolian stratigraphic architectures preserved in different tectonic settings - Grace I.E. Cosgrove; Luca Colombera; Nigel P. Mountney (Earth-Science Reviews, 2023)